PERHELATAN ATRAKSI BUDAYA BAKAR TONGKANG SEBAGAI SALAH SATU ATRAKSI BUDAYA DI RIAU - Melisa Melisa; Rianto M.Si.Par (Jurnal Hospitality dan Pariwisata, 2021)
Bakar Tongkang is one of the cultural attractions in Riau Province, namely Bagansiapiapi City. The Bakar Tongkang cultural attraction event is held annually for generations by the local community due to its unique culture and history.This study was conducted to determine whether the Bakar Tongkang cultural attraction procession in Bagansiapiapi City, Riau Province can be an alternative cultural attraction in Riau Province which is made into a leading attraction. This study uses descriptive qualitative research involving informants representing the Tourism Office, accommodation industry players, transportation industry players, retail store industries, restaurant businesses, street vendors and tourists' views about this cultural attraction procession event as well as the community in Bagansiapiapi City and the organizing committee.From the results of in-depth interviews and observations made by researchers based on in-depth questions, it was found that almost all informants who became sources of information stated that they strongly supported the existence of this cultural attraction event which was carried out regularly every year due to the positive impact of this cultural attraction procession event, namely the impact to the regional economy and Regional Original Income (PAD) and become a leading attraction, in addition to the success of the procession of this cultural attraction, it also has the impact of traffic jams in the city of Bagansiapiapi during the process, rising prices for lodging, food and rickshaw prices as well as other negative impacts, namely waste.